THE USE OF STAD TECHNIQUE TO IMPROVE STUDENTS’ READING COMPREHENSION ACHIEVEMENT - Ratnawati, Dwi (Journal of English Teaching and Learning, 2024)
Reading comprehension is one of dominant aspect before we learn something. The purpose of thisstudy is to develop students’ reading comprehension achievement through Students Team Achievement Division (STAD) strategy in class X MIA 2(Matematika dan Ilmu Pengetahuan Alam) of MA Unggulan located in Banyuwangi. In this study the researcher used Class Action Research (CAR) which consists of five meetings included test. The subject of this research were 36 students and all of them female. Based on preliminary study, it was found that students’ score of reading comprehension were 57.42% while the passing level 75, it means students’ reading comprehension were very low. Besides that the students did not like to read, they said that reading is one of the bored thing to do. From that the researcher used STAD strategy to develop their reading comprehension. In STAD they will fell easily understand the text because it depend on heterogeneous team. If there are some students did not understand about the text, each student who are able to assist must explain to them to make them understand and also build their responsibility to the text. In conclusion, the use of STAD strategy to develop students’ reading comprehension were successful the students’ score improved from 57.42% to 81.18%. In STAD strategy also taught the students to build their responsibility to the text and also make them active during the learning process. So from that they improved.